2018
DOI: 10.1080/09593330.2018.1449903
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient removal from piggery wastewater by Desmodesmus sp.CHX1 and its cultivation conditions optimization

Abstract: Combination of microalgae cultivation and piggery wastewater treatment has become a hot topic in recent years. Nutrient removal from aerated piggery wastewater (APW) by Desmodesmus sp. CHX1 and the optimization of cultivation conditions were investigated in this study. Results indicated that Desmodesmus sp. CHX1 showed an efficient growth in APW, with specific growth rate of 0.26-0.56 d. The biomass yield based on nutrient consumption was 9.65 g biomass/g NH-N and 209.15 g biomass/g total phosphorus (TP) respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…The average removal rates of NH 4 + -N were 1.76-7.92 mg/L/d in OPE, which were clearly higher than those (1.61-4.84 mg/L/d) from the DPE (Table S2). The removal rates achieved in this study agreed with previous studies (2.2-20 mg/L/d) of using other microalgae species for piggery wastewater treatment (Luo et al, 2019). Throughout the experiment, TN removal efficiencies were 42%, 80%, and 89% in 5%, 10% and 20%…”
Section: Nutrient Removal Performancesupporting
confidence: 90%
“…The average removal rates of NH 4 + -N were 1.76-7.92 mg/L/d in OPE, which were clearly higher than those (1.61-4.84 mg/L/d) from the DPE (Table S2). The removal rates achieved in this study agreed with previous studies (2.2-20 mg/L/d) of using other microalgae species for piggery wastewater treatment (Luo et al, 2019). Throughout the experiment, TN removal efficiencies were 42%, 80%, and 89% in 5%, 10% and 20%…”
Section: Nutrient Removal Performancesupporting
confidence: 90%
“…With the development of "Enhanced biological P removal", microalgae-based techniques are attracting increased attention because of the luxury uptake of P by microalgae, accumulating P up to 2-4% of their cell dry weight (Cabanelas et al, 2013;Santos and Pires, 2018;Luo et al, 2019). The cost of wastewater treatment must be counterbalanced with efficacy of P removal and production of microalgal biomass, which further produces a significant economic benefit to society (Prasad et al, 2014;Solovchenko et al, 2019).…”
Section: Recovery Of P From Wastewater and Conversion To Microalgae-d...mentioning
confidence: 99%
“…Microalgae are capable of absorbing inorganic P in excess through storage within their cells in the form of polyphosphate granules (Delgadillo-Mirquez et al, 2016) (Solovchenko et al, 2019). Previous studies reported that microalgae can accumulate large quantities of P (up to 2-4% of their cell dry weight), and thus have potential to be applied as fertilizer after appropriate processing (Cabanelas et al, 2013;Santos and Pires, 2018;Luo et al, 2019). Therefore, reclaiming P from wastewater streams with microalgal cultures is a sustainable and environmental-friendly solution to the shortage of phosphate rock.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of essential nutrients like carbon, nitrogen and phosphorus makes wastewater a suitable medium for microalgae cultivation (Luo et al, 2018). Nitrogen is important for microalgae growth as it aids formation of proteins, enzymes, ATP/ADP etc.…”
Section: Microalgaementioning
confidence: 99%